Serum IgG anti-SARS-CoV-2 Binding Antibody Level Is Strongly Associated With IgA and Functional Antibody Levels in Adults Infected With SARS-CoV-2 - Ye, Xunyan; Angelo, Laura S.; Nicholson, Erin G.; Iwuchukwu, Obinna P.; Cabral de Rezende, Wanderson; Rajan, Anubama; Aideyan, Letisha O.; McBride, Trevor J.; Bond, Nanette; Santarcangelo, Patricia; Rayford, Yolanda J.; Ferlic-Stark, Laura; et al. (Frontiers in Immunology, 2021)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was first reported in December 2019 in Wuhan, China, and then rapidly spread causing an unprecedented pandemic. A robust serological assay is needed to evaluate vaccine candidates and better understand the epidemiology of coronavirus disease (COVID-19). Methods: We used the full length spike (S) protein of SARS-CoV-2 for the development of qualitative and quantitative IgG and IgA anti-S enzyme linked immunosorbent assays (ELISA). A total of 320 sera used for assay development were comprised of pandemic sera from SARS-CoV-2 infected adults (n=51) and pre-pandemic sera (n=269) including sera from endemic human coronavirus infected adults. Reverse cumulative curves and diagnostic test statistics were evaluated to define the optimal serum dilution and OD cutoff value for IgG anti-S and IgA anti-S ELISAs. The IgG and IgA anti-S, and three functional antibodies (ACE-2 receptor blocking antibody, lentipseudovirus-S neutralizing antibody, and SARS-CoV-2 neutralizing antibody) were measured using additional SARS-CoV-2 PCR positive sera (n=76) and surveillance sera (n=25). Lastly, the IgG and IgA anti-S levels were compared in different demographic groups. Results: The optimal serum dilution for the qualitative IgG anti-S ELISA was at 1:1024 yielding a 99.6% specificity, 92.2% sensitivity, 92.9% positive predictive value (PPV), and 99.6% negative predictive value (NPV) at a SARS-CoV-2 seroprevalence of 5%. The optimal serum dilution for the qualitative IgA anti-S ELISA was at 1:128 yielding a 98.9% specificity, 76.5% sensitivity, 78.3% PPV, and 98.8% NPV at the same seroprevalence. Significant correlations were demonstrated between the IgG and IgA (r=0.833 for concentrations, r=0.840 for titers) as well as between IgG and three functional antibodies (r=0.811-0.924 for concentrations, r=0.795-0.917 for titers). The IgG and IgA anti-S levels were significantly higher in males than females (p<0.05), and in adults with moderate/severe symptoms than in adults with mild/moderate symptoms (p<0.001). Conclusion: We developed a highly specific and sensitive IgG anti-S ELISA assay to SARS-CoV-2 using full length S protein. The IgG anti-S antibody level was strongly associated with IgA and functional antibody levels in adults with SARS-CoV-2 infection. Gender and disease severity, rather than age, played an important role in antibody levels.